Optimization of Tilt Angle of a PV System to Get Maximum Generated Power: a Case Study - Taha, Harwan Mohammed; Hameed, Sipan (Kurdistan Journal of Applied Research, 2020)
The amount of solar irradiance falls onto photovoltaic (PV) panels depends highly on the tilt angle between the panels and the horizontal plane. Therefore, this angle must be chosen carefully so that the panels can absorb the largest possible amount of the solar beam. It is more convenient for the panels to be installed with the fixed tilt angle once a month or year as the cost and complexity of the solar tracking systems are high. This research determines monthly and yearly optimum tilt angles for 50 KWp solar system in Duhok city, Duhok Polytechnic University campus (Latitude/Longitude: 36.862, 42.980). Moreover, this work examines the performance of the system with different PV technologies which are Crystalline Silicon, Cadmium Telluride (CdTe), and Copper Indium Selenide (CIS) to determine which one is more convenient for Duhok weather. This work uses the PVGIS simulation tool, and the result shows that the 32.7 degree is the optimum tilt angle for fixed annually adjustment for the mentioned city. While the monthly optimum tilt angles were different for each month (the lowest tilt angle was 1.5? observed in June and the highest tilt angle was 63.9? recorded in December). Regarding PV technologies, the CdTe types generated more annual PV energy than other mentioned types, followed by CIS which produced more output PV energy than Crystalline Silicon.